2017
DOI: 10.1145/3017431
|View full text |Cite
|
Sign up to set email alerts
|

Anonymous or Not? Understanding the Factors Affecting Personal Mobile Data Disclosure

Abstract: The wide adoption of mobile devices and social media platforms have dramatically increased the collection and sharing of personal information. More and more frequently, users are called to make decisions concerning the disclosure of their personal information. In this study, we investigate the factors affecting users’ choices toward the disclosure of their personal data, including not only their demographic and self-reported individual characteristics, but also their social interactions and their mobility patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…(2016) Proceedings of the VLDB Endowment Computer Science Mun et al. (2014) ACM Transactions on Sensor Networks Computer Networks & Communications Nguyen (2020) Internet of Things Internet of Things Applications Perentis et al. (2017) ACM Transactions on Internet Technology Computer Networks and Communications Qi et al.…”
Section: Methodology Developmentmentioning
confidence: 99%
“…(2016) Proceedings of the VLDB Endowment Computer Science Mun et al. (2014) ACM Transactions on Sensor Networks Computer Networks & Communications Nguyen (2020) Internet of Things Internet of Things Applications Perentis et al. (2017) ACM Transactions on Internet Technology Computer Networks and Communications Qi et al.…”
Section: Methodology Developmentmentioning
confidence: 99%
“…A study was conducted by Perentis et al in 2017 in Italy including 63 people with various gender and age, jobs, and education which results that social interaction inferred by mobile phones have a significant impact on willingness (Perentis et al 2017). An online empirical survey was conducted among 913 respondents; they found that both monetary rewards and social rewards positively affect self-disclosure intention, whereas only social rewards positively affect self-disclosure honesty (Wang et al 2017).…”
Section: Literature Review:-mentioning
confidence: 99%
“…Some recent works [33,34] have also investigated the factors affecting users choices toward the disclosure of their personal data. Their works are different from our work, which considered the factors from the perspectives of data features and sampling rates.…”
Section: Related Workmentioning
confidence: 99%